Sunlight desinfects? : free media in weak democracies (2013)
Free media may not favor political accountability when other democratic institutions are weak, and may even bring undesirable unintended consequences. We propose a simple model in which candidates running for office may engage in coercion to obtain votes. A media scandal exposing these candidates entices them to increase their coercion effort to offset the negative shock on their popularity, potentially minimizing or even counteracting the effect of the scandal on their vote share. We provide empirical evidence from one recent episode in the political history of Colombia in which politicians seeking a seat in Congress colluded with illegal armed paramilitary groups to obtain votes, and this collusion was ultimately brought to light by a media scandal. We find that paramilitary-backed candidates exposed before elections get as many votes as those exposed after elections, but their electoral support is more strongly concentrated where coercion is cheaper: in areas with paramilitary presence and weak state capacity. Our results highlight the complementarity between different dimensions of democratic institutions.